Machine learning the Hohenberg-Kohn map for molecular excited states - Yuanming Bai; Leslie Vogt-Maranto; Mark E. Tuckerman; William J. Glover (Nature Communications, 2022)
Density functional theory provides a formal map from the electron density to all observables of interest of a many-body system; however, maps for electronic excited states are unknown. Here, the authors demonstrate a data-driven machine learning approach for constructing multistate functionals.